Antitumoral Properties of Natural Products Volume 2 - Fabiani, Roberto (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Cancer is one of the major causes of death worldwide. It is a multifactorial heterogeneous disease characterized by the transformation of normal cells into malignant cells, which acquire an uncontrolled growth, immortality, invasiveness, and ability to form distant metastasis. Natural bioactive molecules may interfere with these processes and inhibit the carcinogenesis process. In this book, new molecules and extracts, mainly derived from plants, have been described as being able to alter tumor cell behavior and target several abnormal molecular pathways in cancer cells. Among different cancer cells, the more studied include those derived from glioblastoma, osteosarcoma, lung, breast and gastric cancer. These natural products could be an attractive source for the development of new preventative and therapeutic agents against cancer. They may be more selective and have weaker adverse effects compared to conventional chemotherapy drugs that are actually used for cancer treatment. Clinical trials are necessary to demonstrate whether the in vitro and in vivo animal data are reproduced in humans before the application of natural products in cancer prevention and treatment.